2017
DOI: 10.1101/156398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutation rates in seeds and seed-banking influence substitution rates across the angiosperm phylogeny

Abstract: Summary 1) Background. Seed-banking (the ability to persist in the soil over many generations) is usually considered as a dormant stage where genotypes are "stored" as a bet-hedging strategy in response to unpredictable environments. However, seed dormancy may instead have consequences for the integrity of the DNA and generate novel mutations.2) Methods. We address this paradox by building phylogenies based on the plastomes and nuclear ITS of species belonging to ten angiosperm clades. In each clade, the subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 107 publications
0
29
0
Order By: Relevance
“…For example we assume that mutations occur in the seed/egg-bank (a consequence of DNA damage) at the same rate as in the active population. While there is support in plants for this hypothesis [54,55], we have no knowledge of supporting data in Daphnia. If mutations occur in seeds/eggs at a slower rate, we predict the estimation of dormancy to be a conservative lower bound, meaning that the seed/egg-bank is actually longer lived (e.g.…”
Section: Plos Geneticsmentioning
confidence: 72%
“…For example we assume that mutations occur in the seed/egg-bank (a consequence of DNA damage) at the same rate as in the active population. While there is support in plants for this hypothesis [54,55], we have no knowledge of supporting data in Daphnia. If mutations occur in seeds/eggs at a slower rate, we predict the estimation of dormancy to be a conservative lower bound, meaning that the seed/egg-bank is actually longer lived (e.g.…”
Section: Plos Geneticsmentioning
confidence: 72%
“…This is particularly evident across the plant 492 kingdom, in which groups exhibiting very different life histories (e.g. holoparasitism, 493 epiphytism) are linked to having disparate rates of molecular evolution and thus 494 random, local molecular clocks explain better their mode of diversification (Bellot and 495 Renner 2014; Wicke et al 2016;Dann et al 2017). This calls for additional work to 496 account for differences in substitution rates when comparing gene trees.…”
Section: Results 344mentioning
confidence: 99%
“…Phylogenetic approaches can be used to compare the substitution rates of seed banking and nonseed banking sister species (at this evolutionary scale it may be more practical to assess the qualitative aspect of seed banking). A very limited number of studies has shown, using few conserved loci (Whittle, ) or full plastome data (Dann et al ., ), that these rates do not differ significantly from one another, so that the mutation rate in seeds might be assumed to be similar to the mutation rate in plants above ground. As mutation in seeds, hidden to census size estimates, contributes to enhance the discrepancy between N cs and N e (Fig.…”
Section: Seed Banks Affect the Mutation Ratementioning
confidence: 99%